Volume Guarantee Ventilation during Surgical Closure of Patent Ductus Arteriosus - Keszler, Martin; Abubakar, Kabir (American Journal of Perinatology, 2015)
Background Surgical closure of patent ductus arteriosus (PDA) is associated with adverse outcomes. Surgical exposure requires retraction of the lung, resulting in decreased aeration and compliance. Optimal respiratory support for PDA surgery is unknown. Experience with volume guarantee (VG) ventilation at our institution led us to hypothesize that surgery would be better tolerated with automatic adjustment of pressure by VG to maintain tidal volume (VT) during retraction.Objective The objective of this study was to describe ventilator support, VT, and oxygenation of infants supported with VG during PDA surgery.Design/Methods Ventilator variables, oxygen saturation, and heart rate were recorded during PDA surgery in a convenience sample of infants during PDA closure on VG. Pressure limit increased 11% and set VT was 26% lower during lung retraction. Fentanyl and pancuronium/vecuronium were used for anesthesia/muscle relaxation. Longitudinal data were analyzed by analysis of variance for repeated measures.Results Seven infants, 25.4 ± 1.5 weeks and 723 ± 141 g, underwent closure of PDA on VG at a mean age 29.9 days. No air leak, bradycardia, or death occurred. Target VT was maintained with a modest increase in inflation pressure. Oxygenation remained adequate.Conclusions VG avoided hypoxemia and maintained adequate VT with only a modest increase in peak inflation pressure and thus may be a useful mode during PDA surgery.
Keywords: patent ductus arteriosus; surgical closure; volume guarantee ventilation